The Critical Role of Mixed Methods Research in Public Health: Insights from Real-World Case Studies - Elbarsha, Abdelfattah; Gannous , Aiman; Elbakosh , Ibrahim (Libyan Journal of Public Health Practices, 2024)
Mixed methods that combine quantitative and qualitative elements of the approach afford a better capture of the intricacies of health-related issues than any single-method designs. In this review research, we explore the role and importance of mixed methods research in public health by examining how it has been applied in several real-world case studies. The review aims to demonstrate how the mixed methods approach provides an in-depth insight and understanding of public health interventions and their outcomes. Four public health case studies were analyzed to determine the value of mixed methods. The review also goes further to compare the mixed-methods approach with one that is solely quantitative or qualitative. Mixed methods created enormous advantages by putting together statistical rigor with rich contextual insights. Mixed-methods studies can provide a more comprehensive and nuanced view of public health issues than single-method approaches. Mixed methods offered the capacity for in-depth analysis of both measurable outcomes and contextual factors due to their integrative nature with quantitative and qualitative data; hence, we found that complex studies regarding public health could not have been possible without such a method. In addition, the application of mixed methods increased the robustness of public health research by combining empirical data with the community's experiences.